Comparison of infraorbital nerve recovery after open and closed reduction of zygomaticomaxillary complex fractures - Ishaq, Yaser; Noor, Maria; Anwar, Malik Adeel (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Zygomaticomaxillary complex (ZMC) fracture is quite commonly seen fracture in the road side accidents (RTA). It is the second most common fracture after nasal bone fractures. Infraorbital nerve is almost always involved with ZMC fractures which can be treated with open reduction and internal fixation or closed reduction. Methods: The aim of this study was to compare the recovery of infraorbital nerve paresthesia following open reduction and internal fixation verses closed reduction in the management of ZMC fractures. Results: Two groups with n=50 patients each, qualifying our inclusion criteria were selected, examined, reduced by open and closed reduction respectively and followed up. Conclusions: The functional infraorbital nerve recovery was found among 74% patients those who underwent open reduction and internal fixation. While the patients treated with closed reduction the functional nerve recovery was seen in 52%.